Phosphorus adsorption on iron‐coated sand under reducing conditions. Issue 1 (22nd December 2022) - Barcala, Victoria; Jansen, Stefan; Gerritse, Jan; Mangold, Stefan; Voegelin, Andreas; Behrends, Thilo
Abstract: Mitigation measures are needed to prevent large loads of phosphate originating in agriculture from reaching surface waters. Iron‐coated sand (ICS) is a residual product from drinking water production. It has a high phosphate adsorption capacity and can be placed around tile drains, taking no extra space, which increases the farmers' acceptance. The main concern regarding the use of ICS filters below groundwater level is that limited oxygen supply and high organic matter concentrations may lead to the reduction and dissolution of iron (hydr)oxides present and the release of previously adsorbed phosphate. This study aimed to investigate phosphate adsorption on ICS at the onset of iron reduction. First, we investigated whether simultaneous metal reduction and phosphate adsorption were relevant at two field sites in the Netherlands that use ICS filters around tile drains. Second, the onset of microbially mediated reduction of ICS in drainage water was mimicked in complementary laboratory microcosm experiments by varying the intensity of reduction through controlling the oxygen availability and the concentration of degradable organic matter. After 3 yr, ICS filters in the field removed phosphorus under low redox conditions. Over 45 d, the microbial reduction of manganese and iron oxides did not lead to phosphate release, confirming field observations. Electron microscopy and X‐ray absorption spectroscopy did not evince systematic structural or compositional changes; only under strongly reducing conditions did iron sulfides form in small percentages in the outer layer of the iron coating. Our results suggest that detrimental effects only become relevant after long periods of operation. Core Ideas: After 3 years in the field, ICS filters removed P under Mn and Fe reducing conditions. We studied the effect of reducing conditions on P adsorption on ICS with microcosm experiments. For 45 days under different reducing conditions, P was not released after Mn and Fe partial reduction. Most of the crystal structure of the ICS remained unchanged despite Mn and Fe reduction.